Pendeteksian Financial Statement Fraud Berdasarkan Metode Beneish M-Score Pada Perusahaan Manufaktur Di BEI - Urip Wardoyo, Dwi; Hilmi Alrasyid, Arifah; Luthfania Patra, Salma; Randi Kuncoro, Hermawan (Fakultas Ekonomi Universitas Gresik, 2023)
This research aims to analyze and also to test the results using the Beneish M-Score Model to detect fraudulent financial statement. This research also aims to determine the percentage of 20 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period which are classified as non-manipulator, manipulator, and grey companies. The research method used is descriptive quantitative method of variable analysis using the Beneish Ratio Index using five calculation indexes for Days Sales in Receivable Index (DSRI), Gross Margin Index (GMI), Sales Growth Index (SGI), Asset Quality Index (AQI), and Total Accrual To Total Assets Index (TATA). The research results show that the five index calculatin variables are able to distinguish samples of financial statements that are suspected not to be manipulated